Detection of intravascular hemolysis in newborns using urinary carbonic anhydrase I immunoreactivity - Kramer, H; Hulikova, A; Khan, H; Swietach, P (Oxford University Press, 2020)
Background: Mild hemolysis occurs physiologically in neonates, but more severe forms can lead to life-threatening anemia. Newborns in developing regions are particularly at-risk due to the higher incidence of triggers (protozoan infections, sepsis, certain genetic traits). In advanced healthcare facilities, hemolysis is monitored indirectly using resource-intensive methods that probe downstream ramifications. These approaches could potentially delay critical decisions in early-life care, and are not suitable for point-of-care testing. Rapid and cost-effective testing could be based on detecting red blood cell (RBC)-specific proteins, such as carbonic anhydrase I (CAI), in accessible fluids (e.g., urine).